Secure Verification of Location Claims for Mobile Users - Harika, S; Kondabala, Renuka (International Journal of Computer Sciences and Engineering, 2025)
Area based administrations are rapidly winding up monstrously famous. Notwithstanding administrations in light of clients' present area; numerous potential administrations depend on clients of their area history. “Harmful clients may lie about the spatial-impermanent provenance without an effectively masterminded security structure for clients to display their past zones. In this paper, I demonstrate the Spatial-Fleeting provenance Confirmation with Common Evidences (STAMP) conspires”. STAMP is intended for specially appointed portable clients that are producing area proofs for each other in a disseminated setting. In any case, it can stretch much more without trusted versatile clients and remote access focuses. “STAMP ensures the uprightness and non-transferability of the territory proofs and guarantees customers' security. A semi-trusted Confirmation Specialist is used to pass on cryptographic keys in extension which screen the clients against intrigue by a light-weight entropy-based trust in examination air”. This model of execution on the Android stage demonstrates that STAMP is effortlessness as far as computational and capacity assets. Broad recreation tests demonstrate that entropy-based trust display can accomplish high conspiracy discovery precision.